An investigation into the impact of tooth wear on the oral health related quality of life amongst adult dental patients in the United Kingdom, Malta and Australia. (August 2020) - Mehta, S.B.; Loomans, B.A.C.; Banerji, S.; Bronkhorst, E.M.; Bartlett, D.
Abstract: Objective: To investigate the relationship between levels of tooth wear scored using the Basic Erosive Wear Examination (BEWE) and the impact on the quality of life of adult dental patients. Methods: BEWE assessments were performed on 319 new dentate adult patients attending the practices of 5 trained recruiters based in primary care in Malta (120), Australia (118) or the UK (81). Oral impacts on the quality of life were measured using a shortened form of the Oral Health Impact Profile (OHIP-26). Regression analysis were performed, adjusted for age, to estimate the relationship between the variables. Data were expressed as Confidence Intervals (95 % CI), p-values (values <0.05 were considered statistically significant) and adjusted R 2 values. Results: Overall, the sample had a mean age of 42.6 ± 17.1 (range, 18–93 years), a mean cumulative BEWE score of 6.7 ± 4.4 and a mean total OHIP-26 score of 1.84 ± 0.59. For the cumulative sextant BEWE scores, 68.0 % of the participants scored ≤ 8, 24.5 % between 9 and 13 and 7.5 %, ≥ 14. A significant association was found between increasing BEWE score and the overall OHIP-26 total score (effect = 0.028; p = 0.002), implying a higher BEWE to be associated with a larger impact of oral conditions on daily life. Conclusion: Higher levels of tooth wear were significantly associated with a deteriorating oral-health related quality of life amongst the participants. Clinical relevance: When treatment planning for patients with tooth wear, it is appropriate to consider the psycho-social impact of the condition alongside other clinical findings.